If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7/9+b=11/9
We move all terms to the left:
7/9+b-(11/9)=0
We add all the numbers together, and all the variables
b+7/9-(+11/9)=0
We get rid of parentheses
b+7/9-11/9=0
We multiply all the terms by the denominator
b*9+7-11=0
We add all the numbers together, and all the variables
b*9-4=0
Wy multiply elements
9b-4=0
We move all terms containing b to the left, all other terms to the right
9b=4
b=4/9
b=4/9
| 20x-2=25x=12x+30 | | 6+10m=11 | | 2x+13=3(x-4) | | 6h+24=h-6 | | 10x=2=3x+33 | | 8(-5x-4)=7 | | 2x+12-8x=-6 | | 8x-6=54 | | z-(-1.4)=7.2 | | 5(x=8)+3=33 | | 6(x-3)-3=-3(-5x+2)-3x | | 2x-(5)=23 | | 3=2r-3r | | -11=b/2-5 | | 6((7x+7)=7(6x+6) | | 20q=19q+16 | | 12x-3)=(7x+12) | | -9=3j-3 | | -168=7(-3+7b) | | 12x+3-2=25 | | 12x-7=56 | | (4-2x)+55=107 | | 3x+2(4x-6)=x+1 | | 30.16=17.65+5x | | 4(x+6)=8+2x | | x^2+6x=170 | | -9-3v=-10-4v | | 9x-23=4(x-2) | | 3x=-14-10 | | 4−3u=–14 | | 4x+24=8+2x | | -8t^2-15t+11=0 |